The Implementation of Panca Jiwa In Pesantren Agro Nur El Falah Salatiga - Haryo Aji Nugroho; Winarno Winarno; Rizki Parahita Anindi (Indonesian Journal of Religion and Society, 2021)
This study is aimed to describe the implementation of panca jiwa of Agro Nur El Falah Islamic boarding school Salatiga. The data is collected through observation, interview and document. This study shows the concept of the panca jiwa includes sincerity, self-awareness, simplicity, exemplary, compassion. Panca Jiwa has been rule of values in the daily activities of pesantren. However, the implementation of Panca Jiwa has not been maximized at the Pesantren Agro Nur El Falah Salatiga. Several factors inhibiting the implementation of the Five Souls include the lack of cooperation between teachers, the lack of activities that can make students become family to each other, damaged infrastructure and also their personalities at home. Therefore, teachers and senior students must set an example and be more diligent in directing, guiding, educating and supervising students to achieve the desired goals in accordance with the vision and mission of the pesantren.